Life Satisfaction, Self-Care Ability, and Loneliness in Older Adults: A Descriptive and Correlational Survey - Kilic, Huelya Firat; Kahraman, Incihan (Wiley, 2025)
Objective: This study aimed to determine the relationship between life satisfaction, self-care ability, and loneliness in older adults. Materials and Methods: This descriptive-correlational study was conducted on voluntary participants aged 65 years and above who lived in North Cyprus. Personal information form, loneliness scale for elderly, satisfaction with life scale and exercise of self-care agency scale were used for data collection. Results: Older adults in our study had moderate levels of life satisfaction and self-care ability and the level of loneliness was at acceptable levels. Besides, the life satisfaction of the participants was positively correlated with self-care ability and negatively correlated with the level of loneliness. Conclusion: The psychosocial needs of older adults might be evaluated, and social support systems might be enhanced within the context of primary healthcare services. Besides, nurses might play an effective role in planning elderly care by taking the importance of multidisciplinary approaches into consideration.
Keywords: life satisfaction; loneliness; older adults; self-care ability